Molecular Mechanism Underlying the Regulatory Effect of Vine Tea on Metabolic Syndrome by Targeting Redox Balance and Gut Microbiota - Zhou, Xixin; Song, Ying; Zeng, Chaoxi; Zhang, Haowei; Lv, Chenghao; Shi, Meng; Qin, Si (Frontiers in Nutrition, 2022)
Metabolic syndrome (MS) is a metabolic disorder that arises from the increasing prevalence of obesity. The pathophysiology seems to be largely attributable to the imbalance of lipid and glucose metabolism, redox signaling pathways, and gut microbiota. The increased syndromes, such as type 2 diabetes and cardiovascular disease demands natural therapeutic attention for those at high risk. Vine tea, as a traditional medicinal and edible resource rich in flavonoids, especially for dihydromyricetin (DHM), exhibits promising health benefits on the intervention of MS, but the specific molecular mechanism has not been systematically elucidated. The present article aims to summarize the regulatory effects and biological targets of vine tea or DHM on MS, and analyze the underlying potential molecular mechanisms in cells, animals, and humans, mainly by regulating the redox associated signaling pathways, such as Nrf2, NF-κB, PI3K/IRS2/AKT, AMPK-PGC1α-SIRT1, SIRT3 pathways, and the crosstalk among them, and by targeting several key biomarkers. Moreover, vine tea extract or DHM has a positive impact on the modulation of intestinal microecology by upregulating the ratio of Firmicutes/Bacteroidetes (F/B) and increasing the relative abundance of Akkermansia muciniphila. Therefore, this review updated the latest important theoretical basis and molecular evidence for the development and application of vine tea in dietary functional products or drugs against MS and also imputed the future perspectives to clarify the deep mechanism among vine tea or DHM, redox associated signaling pathways, and gut microbiota.